2014
DOI: 10.4238/2014.april.25.8
|View full text |Cite
|
Sign up to set email alerts
|

Screening and functional microarray analysis of differentially expressed genes related to osteoporosis

Abstract: ABSTRACT. We searched for key genes that could accurately predict bone mineral density. The gene expression profile GSE7429 was downloaded from the Gene Expression Omnibus database, which includes 20 samples, 10 with high and 10 with low bone mineral density. The differentially expressed genes (DEGs) were identified with packages in R language. Further, BLASTX was used to obtain COG function classifications of all the DEGs. The GOTM software was used to find DEGs enriched modules. The functions of genes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…6 , spectrin beta, non-erythrocytic 1 (SPTBN1), shared by 2 groups, was a hub connected with other 25 nodes including estrogen receptor 1 (ESR1), neurotrophic receptor tyrosine kinase 1 (NTRK1) and phosphatase and tensin homolog (PTEN), etc. ESR1 is related to low bone mineral density (BMD) in AS 35 , 36 . NTRK1 is involved in the pain mechanism 35 while PTEN could active PI3K/Akt signaling which is related to the bone metabolism of AS patients 37 .…”
Section: Resultsmentioning
confidence: 99%
“…6 , spectrin beta, non-erythrocytic 1 (SPTBN1), shared by 2 groups, was a hub connected with other 25 nodes including estrogen receptor 1 (ESR1), neurotrophic receptor tyrosine kinase 1 (NTRK1) and phosphatase and tensin homolog (PTEN), etc. ESR1 is related to low bone mineral density (BMD) in AS 35 , 36 . NTRK1 is involved in the pain mechanism 35 while PTEN could active PI3K/Akt signaling which is related to the bone metabolism of AS patients 37 .…”
Section: Resultsmentioning
confidence: 99%
“…The single-nucleotide polymorphisms (SNPs) of the NRIP1 gene which modulates transcriptional activity of the oestrogen receptor, were correlative with postmenopausal osteoporosis. 36,37 Chen and Xia 38 showed that there was a close relationship between NRIP1 and BMD in B cells in a microarray study. The expression of IRAK3 is predominantly in peripheral blood leukocytes and induced strongly upon the maturation of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…HGS encodes a protein that regulates endosomal sorting and plays a critical role in the lysosomal transport, recycling, and degradation of ubiquitinated membrane proteins in the multivesicular body, which may be a key machinery for autophagic regulation [ 40 ]. ESR1 is essential for sexual development and reproductive function and is involved in the induction of autophagy in response to toxins [ 41 , 42 ]. Autophagy inhibition can reduce intracellular SNCA aggregation and enhance SNCA secretion, which leads to an exacerbation of the microenvironmental response, including inflammation and cellular damage [ 43 ].…”
Section: Discussionmentioning
confidence: 99%